Pengaruh Pemberian Silase Komplit Berbahan Dasar Hijauan yang Berbeda terhadap Kandungan Glukosa Darah dan Urea Darah Kambing Kacang - Jaimito Fahik; Paulus Klau Tahuk (JAS, 2020)
Utilization of goat fodder can be seen in the absorption of feed nutrients that are in the blood. The consumed food will be absorbed into the blood to flow throughout the body. Blood glucose is used as an indicator of the activity of energy metabolism and utilization of carbohydrates in feed, while blood urea is a compound found in the blood derived from ammonia resulting from protein metabolism.The purpose of this study was to look at the effect of giving complete silage based on different forages on the blood glucose and blood urea content of male goats. The variables measured in this study were blood glucose and blood urea of male goat blood. The materials to be used are forage sorghum, lamtoro, natural grass, king grass, corn flour and pollard as well as materials in laboratory analysis. The method used is a Completely Randomized Design with variations of treatment as follows: T1 = Natural Grass 45% + Leucaena leucocephala 20% + Corn 25% + Brand Pollard 10%, T2 = Sorghum bicolor (L.) Moench 45% + Leucaena leucocephala 20% + Corn 25% + Bran Pollar 10%, T3 = Pennisetum purpuphoides 45% + Leucaena leucocephala 20% + Corn 25% + Bran Pollard 10%. Beset on the results of this study it can be concluded that the blood glucose and blood urea levels of male goats whichwere given a complete silage made from natural grass (T1), Sorghum bicolor (L.) Moench (T2), Pennisetum purpuphoides (T3) gave an unreal effect. Blood glucose and blood urea are produced within normal range.